Promoting safe patient handling is up to us. Issue 4 (25th July 2015) - Unknown
Abstract : The perioperative setting has its own unique challenges for safe patient handling. While an injury prevention program may be the solution to decreasing musculoskeletal exertion injuries, it is up to us to implement the education, equipment, and resources available to promote safe patient handling and prevent injury to ourselves.